Elderly Fall Risk Assessment (Elderly) Scale using Hendrich Falls Fall and Morse Scale - Vivi Armany Dessy; Harmayetty Harmayetty; Ika Yuni Widyawati (Universitas Airlangga, 2013)
Introduction: Incidence of falls in elderly become a serious problem for patients hospitalised with limited activity. There was now the patients instruments to measure risk of fall for elderly patients. The aimed of the study was to examine the differences of risk fall to the elderly by using instrument Hendrich Falls Scale (HFS) and Morse Falls Scale (MFS).Methods: A comparative-longitudinal design was used in this study. The population were elderly patients in the treatment room D2 and D3 Adi Husada’s Hospital. There were 20 elderlys as a respondents which taken by using purposive sampling technique. Dependent variable was the value of measuring the risk of falling and independent variable was the instrument of HFS and MFS. Data were analyzed by using Wilcoxon Signed Rank Test with significance level α≤0.05.Result: The results showed that HFS’s instrument compared with MFS in the fi rst day are equally sensitive on the presented 100%, second day: 80%, third day: 31.3%, fourth day: 20%. HFS specificity of MFS on first day compared only 64% than MFS was 100%. The statistical results tests on the both scale of assessment indicated that there were differences the value on first day p=0.180, second day p=0.58, third and fourth day p=0.001.Conclusion: The use of MFS was more sensitive than HSF for detection of elderly patients with falling risk. The conclution of this results MFS’s instrument was more sensitive to assess elderly with risk of fall because MFS,s points more detailed assessment. It is recommended that elderly patients with falling risk need to assess by using MFS. Further research to focus on the risk of fall assessment using HFS and MFS categories.